Integrasi Sistem Hidrolik Vessel Double Cylinder dan Lengan Penyapu pada Electric Road Sweeper - Kuncoro, Robertus Tirta Kuncoroadi; Sugiyanto, Sugiyanto; Kurniawan, Stephanus Danny; Ikhsan, Ridha (Jurnal Teknologi dan Rekayasa Alat Berat, 2024)
The use of electric road sweeper waste sweeping vehicles can increase effectiveness in waste management. This electric road sweeper research aims to integrate the hydraulic system of the sweeper arm and the double cylinder vessel. The process of designing a hydraulic system diagram uses FluidSIM 4.2 software and carries out mathematical calculations based on collecting data directly in the field. The test results show that when the vessel is unloaded, the movement of the sweep arm hydraulic cylinder when extending is 4.20 m/s and the retract movement is 3.1 m/s, and the movement of the vessel hydraulic cylinder when extending is 11.77 m/s and the movement retract worth 9.4 m/s. When the vessel was given a load of 100 kg, the test results obtained were that the movement of the hydraulic cylinder of the sweep arm during extend was 4.20 m/s and the retract movement was 3.1 m/s, as well as the movement of the vessel's hydraulic cylinder in both extend movements was 12.30 m/s. s and a retract movement of 8.60 m/s. It can be seen based on the results of the tests carried out that the load on the vessel influences the movement speed of the vessel's hydraulic cylinder, this is caused by the influence of gravity.